2011
DOI: 10.1007/s11882-011-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Basophils and Autoreactive IgE in the Pathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous disease that can affect multiple organs. A hallmark of this disease, like for other autoimmune diseases, is the presence of large amounts of autoantibodies. As such SLE is considered to be a B cell disease perpetuated by the expansion of autoreactive T and B cells. The T cells involved have long been considered to be Th1 and Th17 cells as these potent pro-inflammatory cells can be found in the tissues of SLE patients. Recent advances point to a role for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…For instance, IFN‐γ primes human pre‐pure basophils for enhanced histamine release upon FcεRI cross‐linking which is consistent with in vitro and in vivo studies demonstrating an increased IgE‐dependent releasability of human basophils during respiratory virus infection . Besides, our data may also be relevant for the recently suggested role of basophils in the pathogenesis of systemic autoimmune disease in which T H 1 cytokines are involved .…”
Section: Discussionsupporting
confidence: 89%
“…For instance, IFN‐γ primes human pre‐pure basophils for enhanced histamine release upon FcεRI cross‐linking which is consistent with in vitro and in vivo studies demonstrating an increased IgE‐dependent releasability of human basophils during respiratory virus infection . Besides, our data may also be relevant for the recently suggested role of basophils in the pathogenesis of systemic autoimmune disease in which T H 1 cytokines are involved .…”
Section: Discussionsupporting
confidence: 89%
“…As indicated above, murine and human data led us to propose the following working hypothesis: basophils, due to their permanent, systemic and low intensity stimulation, amplify autoantibody production and CIC formation by supporting both autoreactive T and B cells in SLO [46]. This hypothesis supports the notion that basophils have a deleterious role in lupus pathogenesis.…”
Section: Basophil Activation Pathways In Slementioning
confidence: 61%
“…Based on the strength of our observations in vitro, we suggest that excessive type 1 IFN production may be the driving factor of the spontaneous inflammatory disorder exhibited by Rabex-5-deficient mice. Indeed, increased histamine and IgE serum levels, reported in Rabex-5-deficient mice, are also characteristics of type 1 IFNmediated disorders such as systemic lupus erythematous (4,27). This conclusion is further supported by the numerous studies that have linked STAT1, which we have observed to be overactive in Rabex-5-deficient cells, to this disorder (28).…”
Section: Discussionmentioning
confidence: 99%